Historical and national values: language, morality and identity (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article analyzes the concepts of “word” (language), “morality and “identity” in the context of national values. Morality is the moral quality of a person, the rules that guide a person in his choice. Identity is the idea of a person’s belonging to various groups and communities: social, economic, national, professional, linguistic, political, religious, gender, racial and others. Morality is a set of special, spiritual rules governing human behavior, his attitude to other people, to himself, as well as to the environment. At the end of the article, an essay on conscience was attached as a concrete manifestation of the substantive essence of the article.
Keywords: philosophy, word, language, morality, national identity, morality, logos, conscience, thought, thinking, cognition, consciousness